Exploring pilot assignment methods for pilot contamination mitigation in massive MIMO systems - Angelina Misso; Mussa Kissaka; Baraka Maiseli (Cogent Engineering, 2020)
In massive multi-input multi-output (MIMO) antenna system, the performance is restricted by inter-cell interference called pilot contamination. However, acquisition of channel state information for channel estimation introduces overheads of pilots required to estimate the channel frequently, a disadvantage that causes inefficient use of bandwidth. A tradeoff thus exists between the number of pilots required to estimate the channel versus the spectral efficiency. Studies on pilot decontamination using pilot assignment lack consideration of the comparative analysis to determine superior approaches. Limited literature exists on the analysis of the existing pilot assignment techniques. Different techniques exhibit varied performances and influence on resource utilization. The purpose of this study is to analyze various methods of pilot assignment schemes for mitigation of pilot contamination in massive MIMO systems. A systematic review approach is adopted to examine different related works and the adopted methodologies, outcomes, and restrictions to determine the most suitable approaches. This study further demonstrates the impact of coherence interval distribution between the pilots for channel estimation and data transmission. An analysis of a tradeoff between FDD and TDD modes is presented to determine the most suitable for massive MIMO antennas. In addition, the study provides recommendations for future research.